Comprehensive response to Usutu virus following first isolation in blood donors in the Friuli Venezia Giulia region of Italy: Development of recombinant NS1-based serology and sensitivity to antiviral drugs. - Ilaria Caracciolo; Erick Mora-Cardenas; Chiara Aloise; Tea Carletti; Ludovica Segat; Maria Sole Burali; Alexsia Chiarvesio; Vivianna Totis; Tatjana Avšič-Županc; Eloise Mastrangelo; Giuseppe Manfroni; Pierlanfranco D'Agaro; et al. (Public Library of Science (PLoS), 2020)
Surveillance of Usutu virus is crucial to prevent future outbreaks both in Europe and in other countries currently naïve to the infection, such as the Americas. This goal remains difficult to achieve, notably because of the lack of large-scale cohort studies and the absence of commercially available diagnostic reagents for USUV. This work started with the first identification of USUV in a blood donor in the Friuli Venezia Giulia (FVG) Region in Northern-Eastern Italy, which is endemic for West Nile virus. Considering that only one IgG ELISA is commercially available, but none for IgM, a novel NS1 antigen based IgG/M ELISA has been developed. This assay tested successfully for the detection of Usutu virus in blood donors with the identification of a second case of transmission and high levels of exposure. Furthermore, two pan-flavivirus antiviral drugs, that we previously characterized to be inhibitors of other flavivirus infectivity, were successfully tested for inhibition of Usutu virus with inhibitory concentrations in the low micromolar range. To conclude, this work identifies North-Eastern Italy as endemic for Usutu virus with implications for the screening of transfusion blood. A novel NS1-based ELISA test has been implemented for the detection of IgM/G that will be of importance as a tool for the diagnosis and surveillance of Usutu virus infection. Finally, Usutu virus is shown to be sensitive to a class of promising pan-flavivirus drugs.